2019
DOI: 10.1039/c9cy00102f
|View full text |Cite
|
Sign up to set email alerts
|

Inductive and electrostatic effects on cobalt porphyrins for heterogeneous electrocatalytic carbon dioxide reduction

Abstract: Inductive and electrostatic effects were found to both play important roles for heterogeneous electrocatalytic CO2 reduction on cobalt porphyrins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 43 publications
6
65
0
Order By: Relevance
“…Recently, a rigorous study on a series of immobilized Co porphyrin catalysts containing varying peripheral aryl substituents (24, 27-32, Chart 2) showed that both inductive and electrostatic substituent effects impact the catalytic CO 2 electroreduction to CO in neutral aqueous media. 158 In order to minimize the aggregation effects, the catalytic properties were probed at low catalyst loadings using TOF CO as a descriptor of the CO 2 RR activity. As a major finding, the log TOF CO was found to linearly increase with the electron-donating character of the substituent (lower Hammett parameter, s) across the series, in agreement with a rate-determining step involving an electron transfer from the Co center to CO 2 .…”
Section: Cobaltmentioning
confidence: 99%
“…Recently, a rigorous study on a series of immobilized Co porphyrin catalysts containing varying peripheral aryl substituents (24, 27-32, Chart 2) showed that both inductive and electrostatic substituent effects impact the catalytic CO 2 electroreduction to CO in neutral aqueous media. 158 In order to minimize the aggregation effects, the catalytic properties were probed at low catalyst loadings using TOF CO as a descriptor of the CO 2 RR activity. As a major finding, the log TOF CO was found to linearly increase with the electron-donating character of the substituent (lower Hammett parameter, s) across the series, in agreement with a rate-determining step involving an electron transfer from the Co center to CO 2 .…”
Section: Cobaltmentioning
confidence: 99%
“…Sodium bicarbonate (99.5 %) and sodium carbonate (99.5 %) salts, which were used as electrolytes, were purchased from Sigma-Aldrich. The catalyst, Cobalt [5,10,15,20 (tetra-N-methyl-4-pyridyl) porphyrin] tetrachloride (CoTMPyP), was purchased from Porphy-Chem. The CO 2 (99.9 %) and Ar (99.995 %) gases were purchased from Maxima.…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…[13][14][15][16][17][18] However, although solvation factors have been taken into account, theoretical calculations were made using the basic cobalt porphine. [13] In the present work we provide a combined experimental and theoretical analysis on the electrocatalytic capabilities of a water-soluble cobalt porphyrin, Cobalt [5,10,15,20-(tetra-Nmethyl-4-pyridyl) porphyrin] (CoTMPyP), in neutral aqueous solutions. The experiments and calculations were made using CoTMPyP as a positively charged water soluble catalyst taking into account the effects of neutral aqueous environment and electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Nonetheless, while the catalytic properties of Co(II) phthalocyanine (CoPc) have been known for several decades, there are limited examples of highly selective CO 2 R at lower overpotentials. 23,24 Continued research in catalyst modification could bring about the desired properties in phthalocyanine catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…29 Pyridine's other possible role as a peripheral substituent could yield changes to the catalytic properties by either changing the electronic density on the macrocycle or giving another catalytic path versus the one that involves coordination of CO 2 to the Co(II) center. 24,30 Herein, we report the synthesis of a pyridine-substituted cobalt phthalocyanine (CoPc-Pyr) and compare its activity with a non-substituted one (CoPc). We fabricate a composite electrode by supporting these derivatives onto a carbon paper.…”
Section: Introductionmentioning
confidence: 99%